gamma-Al2O3 by Ag L-alpha, hard x-ray photoelectron spectroscopy - Rodriguez Pereira, Jhonatan; Rincon-Ortiz, Sergio A; Ospina, Rogelio (American Institute of Physics, 2022)
Gamma-alumina (gamma-Al2O3) powder was characterized by hard x-ray photoelectron spectroscopy with an Ag L-alpha (2984.2 eV) excitation source. The sample was fixed to a stainless-steel sample holder with copper double-sided adhesive tape. Survey spectrum, C 1s, O 1s, Al 1s, Al KLL, Al 2s, and Al 2p core levels spectra were acquired.
Měření gama-Al2O3 pomocí Ag L-alfa, rentgenové foto-elektronové spektroskopie
Keywords: Alumina; HAXPES; Ag L-alpha excitation; gamma-Al2O3; Alumina; HAXPES; Ag L-alfa excitace; gama-Al2O3